A compact C-band FLASH electron linear accelerator prototype for the VHEE SAFEST project - Giuliano, Lucia; Alesini, David; Cardelli, Fabio; Carillo, Martina; Chiadroni, Enrica; Coppola, Massimiliano; Cuttone, Giacomo; Curcio, Alessandro; De Gregorio, Angelica; Raddo, Roberto Di; Faillace, Luigi; Farina, Stefano; et al. (Frontiers in Oncology, 2025)
FLASH therapy, a novel cancer treatment technique, aims to control tumor growth, sparing the healthy tissue from radiation damage and thus increasing the therapeutic ratio. Translating FLASH therapy into clinical practice, especially for treating deep-seated tumors, necessitates achieving Very High-Energy Electron (VHEE) levels within the 50-250 MeV range. In 2022 Sapienza University, in collaboration with INFN, launched the SAFEST project, a compact C-band 100 MeV Ultra-High Dose Rate (UHRD) radiation source for the treatment of deep-seated tumors, which was partially funded by Italian PNRR (Next Generation EU). A C-band linac prototype at lower energy, with an electron pulse of 100 nC and repetition frequency <200 Hz, is being developed to test the key choices and technology of a VHEE machine. This paper provides insights into the design strategy of the prototype, discussing the optimization of the main RF and electron beam parameters. The expected dose profiles are also shown and discussed. The progress of this innovative linac represents a step forward in the realization of a C-band compact FLASH VHEE source for cancer treatment.